Capa, créditos e sumário - Batista, Amanda Damasceno; Cordeiro, Felipe; Moraes, Otávio Augusto Oliveira; Silva, Rafael Guimarães Tavares; Vieira, Tiago de Holanda Padilha; Xavier, Clarissa (Em Tese, 2020)
.